RESPON ORANGTUA TERHADAP SISTEM DARING (DALAM JARINGAN) DI SD MUHAMMADIYAH IV PEKANBARU - Deni Kurniawan Deni Kurniawan; Achmad Hidir Achmad Hidir (JISOS: JURNAL ILMU SOSIAL, 2022)
For children aged 7 to 12 years, students who are still classified as children, they want to play more than study and students do not understand how to learn via the internet. Children do not know how to process the learning system with the internet. Parental attention is needed by children to direct and demonstrate the learning process through the internet. The purpose of this study is to determine the response of parents to the application of online (in the network) and to determine the level of success that occurs in the implementation of online (in the network) at SD Muhammadiyah IV Pekanbaru. This study uses a descriptive quantitative approach, data collection using research instruments, quantitative/statistical data analysis with the aim of testing the established hypothesis. The research hypothesis proposed in this study will be tested using statistical methods. The underlying reason is that statistical methods work by using numbers to produce quantitative data. The results of the study prove that children's development is successful in the system of learning in the network, according to Cognitive, Affective, and Conative terms. Influenced by the relationship of parents who teach from home to demonstrate the learning process on the internet. The way of the learning process, the direction of the system and others.